Effect of Season on Success of Air Layering in Water Apple in Red Laterite Zone of West Bengal - Ghosh, S N (Journal of Horticultural Sciences, 2008)
An experiment was conducted during 2004-05 on farmers' field at Jhargram to work out optimum time for air layering in water apple. Results revealed that air layering performed during June and July resulted in highest rooting success (100%) with maximum field establishment (100%). Considering overall performance, the months of June and July can be recommended for air layering in water apple in red laterite zone of West Bengal.
Keywords: Air Layering; Water Apple; Season; West Bengal